Immune Thrombocytopenic Purpura in Children and Adults: A Comparative Retrospective Study in IRAN - Sajedeh Saeidi; Kaveh Jaseb; Ali Amin Asnafi; Fakher Rahim; Fatemeh Pourmotahari; Samira Mardaniyan; Homayon Yousefi; Arash Alghasi; Mohammad Shahjahani; Najmaldin Saki (International Journal of Hematology-Oncology and Stem Cell Research, 2014)
Background: Immune thrombocytopenic purpura (ITP) is an autoimmune disease that can cause bleeding disorders in patients, and presents in acute and chronic forms. The acute form is frequently seen in children, but the chronic form mainly inflicts adults. There are differences and similarities in clinical and laboratory findings of the disease between children and adults. We study these differences and similarities in these two groups of patients with ITP. Methods: In this study, we retrospectively evaluated the clinical and laboratory data of 323 ITP cases within three years. None of our patients had a history of thrombocytopenia. Patients were classified into two groups of children (3 months to 16 years of age) and adults (≥ 16 years). Data analysis was conducted using SPSS software, and the analysis results were compared between the two age groups. Results: Overall, the disease prevalence was higher in women than men, but the prevalence of childhood ITP was higher in males than females. The prevalence of initial symptoms including petechiae, purpura and ecchymosis was 60.5% and 61%, respectively in all patients, but severe bleeding rarely occurred in patients (28.8%). 30.5% of patients had a history of infection before developing ITP, and the children had a higher frequency of infection (80.8%). Before treatment, the mean platelet count in adults and children was 33000/μL and 35000/μL, respectively. Conclusion: Comparison of data in children and adults with ITP indicated similarities and differences in clinical and laboratory findings between the two groups with differences in prevalence, bleeding symptoms, initial platelet count and infection history.